A STUDY ON THE EFFECT OF EXACERBATIONS ON THE QUALITY OF LIFE OF PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE (World Journal of Current Medical and Pharmaceutical Research, 2020)
Aim:  The main aim of this study is to evaluate the effect of exacerbations on the quality of life of the patients with chronic obstructive pulmonary disease.Materials and Methods: Patients of both the genders and with an age of above 18 years of patients who were diagnosed with COPD were included in this prospective study. Modified British Medical Research Council (m-MRC) Dyspnoea Scale was used to establish functional impairment due to shortness of breath in the study participants. Saint George's Respiratory Questionnaire (SGRQ) was also used to assess the patient’s overall health and quality of life-based on self-report.Results: Among the 110 study participants, 87.3% were males and 12.7% were females. It was observed that majority of the patients were in the age group 51-60 years (43.6%). The most frequently observed co-morbidities were hypertension (22.7%) followed by diabetes mellitus (19.1%). Most of the patients were observed to be with m-MRC grade-3 (42.7%) followed by m-MRC garde-2 (39.1%). The SGRQ score was observed to be increased with increase in the frequency of exacerbations.Conclusion: Clinical Pharmacist should take the responsibility in providing effective evidence based therapeutic recommendations for the better management and well being of the COPD patients.